The Ocean Economy in SIDS – Environmental Taxation - Majewska, Julia (Gospodarka oceaniczna w krajach SIDS – opodatkowanie środowiskowe, 2024)
Over the years, with the increase in consumerism and accelerated globalisation, there has been a growing trend in the use of water resources, including oceans. This results in, among other things, pollution. In order to assess the existing state of the oceans and the instrument that can mainly contribute to the protection of water resources, environmental taxes are used. The objective of this study was to evaluate the significance of environmental taxes in SIDS (Small Island Developing States) with particular emphasis on ocean-related taxes. The article describes the current threats to the ocean economy, in particular pollution and loss of biodiversity. Based on the analysis of the literature and quantitative data, it can be concluded that the number of taxes related to the oceans in SIDS is marginal. Tax revenues from environmental taxes in SIDS are relatively small compared to other countries. The research methods used in the paper are literature analysis, analysis of existing data and the inference method.
Ekonomia XXI Wieku = Economics of the 21st Century, 2024, Nr 27, s. 1-9
Keywords: ocean economy; tax revenues; SIDS; gospodarka oceaniczna; dochód z podatków; środowisko